Synovial Fluid Biomarkers for Periprosthetic Infection - Deirmengian, Carl (Springer-Verlag, 2010)
BACKGROUND: We have previously described a unique gene expression signature exhibited by synovial fluid leukocytes in response to bacterial infection, identifying a number of potential biomarkers for infection. However, the diagnostic performance of these potential biomarkers in an immunoassay format is unknown. QUESTIONS/PURPOSES: We therefore evaluated the sensitivity, specificity, and accuracy of several potential synovial fluid biomarkers for infection, and compared them to current standards of testing for periprosthetic infection. METHODS: We prospectively collected synovial fluid from 14 patients classified as having a periprosthetic infection and 37 patients classified as having an aseptic failure. The synovial fluid samples were tested for 23 potential biomarkers for periprosthetic infection. We then determined differences in biomarker levels between infected and aseptic groups, then computed the sensitivity, specificity, positive predictive value, negative predictive value and accuracy for select biomarkers, and finally compared those to current standard tests for infection. RESULTS: Twelve synovial fluid biomarkers had substantially higher average levels in the synovial fluid of infected versus aseptic patients. Synovial fluid levels of IL-1 were a mean of 258 times higher in patients with a periprosthetic infection compared to patients having revision for aseptic diagnoses. Synovial fluid IL-1 and IL-6 levels correctly classified all patients in this study with a sensitivity, specificity, positive predictive value, negative predictive value and accuracy equal to 1. Several markers tested in this study outperformed the ESR and CRP tests. CONCLUSIONS: Patients with a periprosthetic infection have elevated levels of numerous synovial fluid biomarkers, when compared to patients with aseptic diagnoses. Several of these biomarkers exhibited nearly ideal sensitivity, specificity, and accuracy in this study, suggesting that synovial fluid biomarkers could be a valuable tool for diagnosing periprosthetic infection. LEVEL OF EVIDENCE: Level III, prognostic study. See Guidelines for Authors for a complete description of levels of evidence.